The Novel Aminomethylcycline Omadacycline Has High Specificity for the Primary Tetracycline-Binding Site on the Bacterial Ribosome - Corina G. Heidrich; Sanya Mitova; Andreas Schedlbauer; Sean R. Connell; Paola Fucini; Judith N. Steenbergen; Christian Berens (MDPI AG, 2016)
Omadacycline is an aminomethylcycline antibiotic with potent activity against many Gram-positive and Gram-negative pathogens, including strains carrying the major efflux and ribosome protection resistance determinants. This makes it a promising candidate for therapy of severe infectious diseases. Omadacycline inhibits bacterial protein biosynthesis and competes with tetracycline for binding to the ribosome. Its interactions with the 70S ribosome were, therefore, analyzed in great detail and compared with tigecycline and tetracycline. All three antibiotics are inhibited by mutations in the 16S rRNA that mediate resistance to tetracycline in Brachyspira hyodysenteriae, Helicobacter pylori, Mycoplasma hominis, and Propionibacterium acnes. Chemical probing with dimethyl sulfate and Fenton cleavage with iron(II)-complexes of the tetracycline derivatives revealed that each antibiotic interacts in an idiosyncratic manner with the ribosome. X-ray crystallography had previously revealed one primary binding site for tetracycline on the ribosome and up to five secondary sites. All tetracyclines analyzed here interact with the primary site and tetracycline also with two secondary sites. In addition, each derivative displays a unique set of non-specific interactions with the 16S rRNA.